Innovative use of autologous fat grafting and regenerative therapies in the surgical management of dermatological scarring disorders: a systematic review of functional and aesthetic outcomes - Cevallos, Karla Enith Guamán; Pacheco, Elizabeth Arellano; Galindo, Andres Felipe Santodomingo; Alfonso, González Mercado Zeus Edrian Daniel; Gastelum, Jorge Luis Rivera; Mora, Jeremy Paolo Flores; López, Ricardo Uriel Maldonado (International Journal of Research in Medical Sciences, 2025)
A systematic strategy was adopted to evaluate efficacy of autologous fat grafting and regenerative therapies such as platelet-rich plasma (PRP) or stromal vascular fraction (SVF) for the management of dermatological scarring disorders. In methodology, selected databases are PubMed, Scopus, Web of Science and Cochrane Library so total of 25 studies were selected involving 2,130 patients with hypertrophic, keloid, or atrophic scars. We conducted meta-analysis and revealed 35% improvement in scar pliability and a 40% enhancement in aesthetic appearance as assessed by validated scales. In functional outcomes such as relief from pain and itching was improved by 68% and patient satisfaction scores increased significantly with minor complications such as transient edema and localized infection reported in 8% of cases. Regenerative potential of fat grafting amplified by PRP and SVF show ability to promote dermal remodeling, angiogenesis and tissue repair. In results, fat-based therapies demonstrated better functional and aesthetic results when compared to traditional treatments and our results highlight more extensive, superior randomized controlled studies are needed to validate effectiveness and improve procedures. We illustrated how autologous fat grafting and regeneration techniques can improve patient satisfaction and results in dermatological scarring.